Removal of Aqueous Pb(II) Using Low-Cost Agricultural Wastes Modified by 3-Aminopropyltrimethoxysilane - Ding, Zhuhong; Yu, Rui; Hu, Xin; Zhang, Yufeng (Asian Journal of Chemistry, 2015)
In order to develop the low-cost and high efficient absorbents, agricultural by-products e.g., peanut hulls, soybean shells and grapefruit peels were chemically modified with 3-aminopropyltrimethoxysilane after the saponification using 17.5 % NaOH. Chemical modification was confirmed by infrared spectra and N contents. The optimum adsorption parameters for Pb(II) were around 4.5 for pH and 2 g L-1 for ratio of solid to liquid. The kinetic adsorption fitted well with the pseudo-second order kinetic model and the isotherm adsorption fitted well with Langmuir adsorption model. The maximum absorption capacities of chemically-modified peanut hulls, soybean shells and grapefruit peels were 32.9, 75.8 and 154 mg g-1, respectively. More than 90 % Pb(II) can be desorbed from modified biosorbents using 1 mol L-1 HCl solution. Chemically-modified grapefruit peels exhibited higher absorption capacities and can be used as potential the low-cost and high efficient absorbents for the removal of Pb(II) from wastewater.